2012
DOI: 10.1371/journal.pone.0032145
|View full text |Cite
|
Sign up to set email alerts
|

The Axonal Guidance Receptor Neogenin Promotes Acute Inflammation

Abstract: Neuronal guidance proteins (NGP) were originally described in the context of axonal growth and migration. Yet recent work has demonstrated that NGPs also serve as guidance cues for immune competent cells. A crucial target receptor for NGPs during embryonic development is the neogenin receptor, however its role during acute inflammation is unknown. We report here that neogenin is abundantly expressed outside the nervous system and that animals with endogenous repression of neogenin (Neo1−/−) demonstrate attenua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
(36 reference statements)
1
14
0
Order By: Relevance
“…For example, inflammation is reduced in neogenin knockout mice in models of peritonitis, lung injury and ischemia-reperfusion. Thus, contrary to its reported anti-inflammatory effects, these findings support the interpretation that Netrin-1 has pro-inflammatory properties via interactions with distinct neogenin-expressing leukocyte subsets (2527). Our new findings in this report indicate that the key function of Netrin-1 on CD4+ T lymphocytes is to induce chemokinesis, and that its effect on either chemoattraction or chemorepulsion are a function of random directional migration and/or additional factors.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…For example, inflammation is reduced in neogenin knockout mice in models of peritonitis, lung injury and ischemia-reperfusion. Thus, contrary to its reported anti-inflammatory effects, these findings support the interpretation that Netrin-1 has pro-inflammatory properties via interactions with distinct neogenin-expressing leukocyte subsets (2527). Our new findings in this report indicate that the key function of Netrin-1 on CD4+ T lymphocytes is to induce chemokinesis, and that its effect on either chemoattraction or chemorepulsion are a function of random directional migration and/or additional factors.…”
Section: Discussionsupporting
confidence: 75%
“…This effect was reported to be mediated in part via its effects on the local infiltration of neutrophils and macrophages (16, 18, 20, 34). However, more recent studies indicate that the expression of pro-migratory neogenin may be critical in the functional outcome of an inflammatory response (2527, 35, 36). For example, inflammation is reduced in neogenin knockout mice in models of peritonitis, lung injury and ischemia-reperfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was not demonstrated that the formation of this complex was dependent on WIP phosphorylation by PKCθ (Krzewski et al, 2006). Interestingly, it has been recently published the kinome of NK cells activated by CD16 or simultaneous CD244 and DNAM-1 ligation, being PKC-θ identified as the only PKC isoform that increase phosphorylation upon receptor ligation (König et al, 2012). …”
Section: A Role For Pkcθ In Nk Cell Degranulation?mentioning
confidence: 99%
“…The receptor of Netrin-1 and RGM-A, Neogenin 1 (Neo1), plays an important role during the onset of acute inflammation. [51][52][53] A recent report identified a previously unknown role of Neo1 during the resolution of inflammation and during regeneration. 54 Functional inhibition of Neo1 stimulated the apoptosis of human PMNs and activated find-me signals on apoptotic PMNs as well as findme and eat-me receptors on human MΦs.…”
Section: Impact Of Neogenin On Inflammation Resolution and Tissue Regmentioning
confidence: 99%